(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
The rapid expansion of digital technologies and Internet-based services has significantly increased the exposure of ordinary users to cyber risks. Everyday activities such as online communication, financial transactions, and data storage are now heavily dependent on digital platforms, which makes personal information vulnerable to various cyber threats. This paper examines the core cybersecurity issues faced by non-professional users and analyzes essential protective measures, including secure authentication practices, recognition of deceptive online attacks, protection against malicious software, timely system updates, and responsible Internet usage. The study highlights that improving user awareness and adopting basic security behaviors play a decisive role in minimizing cyber threats and ensuring data protection in the digital environment.